2023
DOI: 10.3390/molecules28052200
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Eugenol Nanoemulsion Alleviates the Negative Effects of Experimental Coccidiosis on Broiler Chicken’s Health and Growth Performance

Abstract: The present study investigated the protective efficacy of dietary supplementation with clove essential oil (CEO), its main constituent eugenol (EUG), and their nanoformulated emulsions (Nano-CEO and Nano-EUG) against experimental coccidiosis in broiler chickens. To this aim, various parameters (oocyst number per gram of excreta (OPG), daily weight gain (DWG), daily feed intake (DFI), feed conversion ratio (FCR), serum concentrations of total proteins (TP), albumin (ALB), globulins (GLB), triglycerides (TG), ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Our data indicated that both oregano oil and clove oil improved broiler growth performance including weigh gain and feed conversion ability, which was consistent with previous studies ( Nawarathne et al, 2022 ; Zaazaa et al, 2022 ; Youssefi et al, 2023 ). Although broilers are considered to have less sense of taste than other mammalian production animals due to the shortage of sweet sensing gene T1R2 ( Shi and Zhang, 2006 ), essential oils could improve broiler nutrient utilization through other mechanisms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data indicated that both oregano oil and clove oil improved broiler growth performance including weigh gain and feed conversion ability, which was consistent with previous studies ( Nawarathne et al, 2022 ; Zaazaa et al, 2022 ; Youssefi et al, 2023 ). Although broilers are considered to have less sense of taste than other mammalian production animals due to the shortage of sweet sensing gene T1R2 ( Shi and Zhang, 2006 ), essential oils could improve broiler nutrient utilization through other mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…In theory, the phenol ring in essential oil could improve the antioxidant ability by degrading oxyradical in vitro ( Bhalla et al, 2013 ). The improvement of antioxidant capacity was also reported in live broiler trials ( Paraskeuas et al, 2017 ; Zhang et al, 2022b ; Youssefi et al, 2023 ). Nevertheless, the inconsistent effects in serum oxidant capacity were also reported in other trials ( Gordillo-Jaramillo et al, 2021 ; Choi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Eimeria infection symptoms include malnutrition, enteritis, and, in severe cases, mortality for some Eimeria species, endangering the health of birds and their economic production ( Youssefi et al, 2023 ). Food security and the global agroeconomy will face significant challenges due to this pathogenic protozoan and its detrimental impact on production due to the ever-increasing human need for protein resources from poultry ( Teng et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils and vitamins: Essential oils and vitamins are effective parts of plants and have potent immunomodulatory, antifungal, and antioxidant activities (Dudko et al, 2018;Bangulzai et al, 2022;Fan et al, 2022;Pelvan et al, 2022;Raza et al, 2022;Iordache et al, 2023). These activities give great help in reducing the signs of coccidiosis (Rizwan et al, 2021;Adhikari et al, 2020;Youssefi et al, 2023). Multiple researchers have indicated that essential oils and vitamins can be helpful in controlling coccidiosis .…”
Section: Botanical Approaches To Control Coccidiosis Tanninsmentioning
confidence: 99%